Pattern of Constipation and Response to Polyethylene Glycol in Children - Saha, Sudip; Bose, Kallol; Das, Kallol; Mridha, Dhrubojyoti; Das, Ira; Mondal, Piyasi (Journal of Nepal Paediatric Society, 2017)
Introduction: Constipation is a common problem in children with worldwide prevalence between 0.7% and 29.6%. Materials and Methods: Total number of children was 232 out of which 16 were discarded due to loss in follow up. Inclusion criteria: Any child aged one month to ten years presenting with constipation. We used NASPGHAN definition of constipation. Exclusion criteria: Critically sick and hemodynamically unstable patients were excluded from the study. Data were collected for age, sex, duration of constipation, symptoms and signs such as stool frequency, stool consistency, pain during defecation, presence of blood in stool, fecal and urinary incontinence, and presence of fecal impaction or an abdominal mass. Clinical evaluation (history and physical examination) of all patients was done by the same physician to avoid bias in clinical finding. Polyethylene glycol (PEG) was tried in all patients in a dose of 0.3 to 2.1g/kg. Response was defined as passage of at least one semisolid stool without discomfort with use of PEG for at least 4 weeks. Results: In our prospective study done on 232 patients with constipation over three year period (dividing patient’s into1month to 5months, 6months to 5year and 6 years to 10 years) revealed that constipation is mostly prevalent in 6 months to 5 year age group with slight male preponderance. Most of them had symptom onset after six months of age. Commonest symptom was hard stool in general (79.6%) but prevalence of pain abdomen increases with age and peaks in above five year group. Commonest sign is palpable fecal mass. Complications-urinary dysfunction, fecal incontinence, fissure are common in older age group. Functional constipation was the commonest cause (96.2%). Hirschprung disease was diagnosed in 1.4%. Polyethylene glycol shows good response in above 6 months of age groups. Conclusion: Functional constipationis the commonest cause of constipation. Mostly affected group is six months to five years. Polyethelene Glycol is an effective treatment especially after six months. J Nepal Paediatr Soc 2016;36(3):263-267.